Correlation Between Adult Tobacco Smoking Prevalence and Mortality of Coronavirus Disease-19 Across the World - Nadya Magfira; Helda Helda (Acta Medica Indonesiana)
Background: Coronavirus disease 2019 (COVID-19) is a global pandemic spreading worldwide. Limited studies showed that smokers were at higher risk of having severe complications and higher mortality. We aimed to analyze the possible correlation between adult tobacco smoking prevalence and COVID-19 mortality all over the world. Methods: this correlation study involved a linear regression to analyse the correlation between smoking prevalence data in adults and COVID-19 Case Fatality Ratio (CFR) in countries with 1000 confirmed COVID-19 cases on May 3, 2020. Results: seventy-five countries included with median CFR 3.66%. There was no relationship between adult male or female smoking prevalence and COVID-19 mortality in all over the countries. The multivariate analysis showed p-values of 0.823 and 0.910 for male and female smoking prevalence, respectively. However, in lower-middle-income countries (LMIC), there was a positive correlation between the prevalence of adult male smoking with the mortality of COVID-19. Each increment of one percentage of adult male smoking prevalence was associated with increase in COVID-19 CFR by 0.08% (95% CI 0.00%-0.15%, p=0.041). Conclusion: there is correlation between the prevalence of adult male smoking and the CFR of COVID-19 in lower middle-income countries. Based on these findings, strengthening of tobacco control policies is essential to reduce the impact of the COVID-19 pandemic especially in LMIC. This still warrants further studies.